Analisis Prosedur Sistem Informasi Akuntansi pada Siklus Penggajian Terhadap Karyawan: Studi Kasus BPDAS Jeneberang Saddang - Devita Natalia; Nuraisyiah; Masnawaty Sangkala (VISA: Journal of Vision and Ideas, 2024)
A payroll accounting system is really needed in a company that can deal directly with employees. The payroll system functions in managing payment transactions for services carried out by employees who have a manager level position. Payroll-related activities (information regarding recruitment, dismissal, transfer, training, etc.) and collection of information regarding the use of employee time that occurs every day. However, the actual processing of payroll only occurs periodically because in most organizations employees are paid weekly, biweekly, or monthly rather than daily. Therefore, payroll is a continuous application that is processed in batch mode. The subject of this research is one of the administrative staff informants at the BPDAS Jeneberang Saddang office, while the results of this research are using documentation guidelines and interview guidelines taken using direct interview and documentation techniques. Data collection is carried out using a direct acquisition system from the parties concerned. Data analysis was carried out using qualitative descriptive analysis techniques. The research results show that the payroll system that occurs at the BPDAS Jeneberang Saddang office is in accordance with the Operational Procedure System (SOP) that has been established by the Ministry of Finance, namely the payroll system that is implemented at the BPDAS Jeneberang Saddang office is good in terms of providing documents relating to payroll system. The payroll system used by the BPDAS Jeneberang Saddang office is technology-based using the GPP (Central Civil Servant Salary) application system and other supporting documents such as changes to employee salary lists, making SPP (Payment Request Letters), SSP (Tax Payment Letters), SPM ( Payment Order), and finally SP2D (Funds Disbursement Order).